Heavy Metal Contaminations in Herbal Medicines: Determination, Comprehensive Risk Assessments, and Solutions - Luo, Lu; Wang, Bo; Jiang, Jingwen; Fitzgerald, Martin; Huang, Qin; Yu, Zheng; Li, Hui; Zhang, Jiqing; Wei, Jianhe; Yang, Chenyuyan; Zhang, Hui; Dong, Linlin; et al. (Frontiers in Pharmacology, 2021)
Heavy metal contamination in herbal medicines is a global threat to human beings especially at levels above known threshold concentrations. The concentrations of five heavy metals cadmium (Cd), lead (Pb), arsenic (As), mercury (Hg) and copper (Cu) were investigated using Inductively Coupled Plasma Optical Mass Spectrometry (ICP-MS) with 1773 samples around the world. According to Chinese Pharmacopoeia, 30.51% (541) samples were detected with at least one over-limit metal. The over-limit ratio for Pb was 5.75% (102), Cd at 4.96% (88), As at 4.17% (74), Hg at 3.78% (67), and of Cu, 1.75% (31). For exposure assessment, Pb, Cd, As, and Hg have resulted in higher than acceptable risks in 25 kinds of herbs. The maximal Estimated Daily Intake (EDI) of Pb in seven herbs, of Cd in five, of Hg in four, and As in three exceeded their corresponding Provisional Tolerable Daily Intakes (PTDI). In total 25 kinds of herbs present an unacceptable risk as assessed with the HQ (Hazard Quotient) or HI (Hazard Index). Additionally, the carcinogenic risks (CR) were all under acceptable limits. Notably, As posed the highest risk in all indicators including EDI, HI, and CR. Therefore further study on enrichment effect of different states of As and special attention to monitoring shall be placed on As related contamination.